PENGEMBANGAN STORYBOARD APLIKASI SAKUPINTAR UNTUK MENDUKUNG PEMBELAJARAN LITERASI KEUANGAN SISWA - Agnisa Widayanti; Gayatria Oktalina; Jaya, Fitra; Yati, Yati; kadarisman, kadarisman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop the storyboard of the Saku Pintar application as an initial design for an Artificial Intelligence (AI)-based personal financial management application to support financial literacy. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, and validation stages. A needs analysis was conducted through interviews with teachers and students of MA Plus Al-Fattah Blora to identify user requirements for a financial management application and financial literacy learning. The developed storyboard integrates several key features, including transaction recording, savings planning (dream goals), learning cards, and AI-based personalized recommendations. The feasibility of the storyboard was evaluated by subject matter experts, media experts, and prospective users. The validation results indicated that the storyboard achieved feasibility scores of 94% from subject matter experts, 96% from media experts, and 92% from users, with an overall average score of 94%, which falls into the “highly feasible” category. The findings suggest that the Saku Pintar application storyboard is highly suitable as a foundation for developing an application that supports financial literacy and personal financial management.